Transfer of gene conferring herbicide bialaphos resistance into buckwheat plants - Rubtsova, M.A.; Levenko, B.A.; Taranenko, L.K.; Stekhin, I.N.; Sayaz, L.I. (Биополимеры и клетка, 1997)
Bar gene conferring resistance to herbicide bialaphos (phmphinothricin) was cloned from Streptomyces hygroscopicus. Bar gene under 35S promoter of cauliflower mosaic virus was introduced in binary pBin19 vector and constructed plasmid was transferred into Agrcbacterium tumefaciens strain. Conditions of genetic transformation of cultivated buckwlwat and interspecific hybrid Fagopirum esculentum X F. tataricum were worked out. Buckwheat explants were inoculated by the strain with a plasmid carrying bar gene nearby NPTII gene. Molecular analysis of 8 regenereted plants that were selected for kanamycin resistance was performed. 5 plants gave positive signal by dol- and Southern hybridization using as a probe DNA fragment with bar gene that is an evidence of integration of bar gene into plant genome. Transformed plants grow and rooted at Basta concentrations in the medium, that totally inhibited nontransformed plants. Із Streptomyces hygroscopicus клонували bar-ген, який визначає стійкість до гербіціду біалафосу (фосфінотрицину). Ген під контролем 35S-промотора вірусу мозаїки цвітної капусти було введено у бінарний вектор рВin19 для трансформації рослин. Одержану рекомбінантну плазміду перенесено до штаму 3850 Agrobacterium tumefaciens. Підібрано умови трансформації культурної гоечхи і міжвидового гібрида Fagopyrum esculentum х F. tatarium. Експланти гречки інокулювали агробактеріальним штамом, у якому bar-ген знаходиться на Тi плазміді поруч з NPTII геном. Здійснено молекулярно-біологічний аналіз восьми регенерантів, які пройшли канаміщновий відбір. П'ять рослин дали позитивну радіоавтографічну відповідь при дот- і Саузерн-гібридизації з міченим зондом, який несе bar-ген, що свідчить про інтеграцію цього гена в геном рослин. Трансформовані рослини росли і утворювали коріння при концентрації гербіциди басти в середовищі, яке повністю пригнічувало нетрансформовані рослини, Из Streptomyces hygroscopicus клонировали bar-ген, определяющий устойчивость н гербициду биалафосу (фосфинотрицину). Ген под контролем 35S-промотора вируса мозаики цветной капусты был введен в бинарный вектор рВіп!9 для трансфор-мании растений. Полученная рекомбинантная плазмида перенесена в штамм 3850 Agrobacterium tumefaciens. Подобраны условия трансформации культурной гречихи и межвидового гибрида Fagopyrum esculentum X F. taiaricum. Экспланты гречихи инокулировали агробактериальным штаммом, в котором bar-ген находился на Тi плазмиде рядом с геном NPTII Проведен молекулярно-биологический анализ восьми регенераншов, прошедших канамициновый отбор. Пять растений дали положительный радиоавтографический ответ при дот- и Саузерн-гибридизации с меченым зондом, несущим bar-ген, что свидетельствует об интеграции этого гена в геном растений. Трансформированные растения росли и образовывали корни при концентрации гербицида басты в среде, полностью ингибирующей не трансформированные растения.